Competitive vs Collaborative Clinical Nutritionists: The European Clinical Nutrition Market - Garduno-Diaz; Frost (European Journal of Applied Sciences, 2022)
The European clinical nutrition market is a diverse and competitive industry which would significantly benefit from more conversations about and action towards collaboration between specialists. So far, investment in market research has been focussed on competition and innovation. While collaboration is considered key for the progress of the industry, it is often not prioritized. Professionals, students and new entrants into the European clinical nutrition market, as well as the lay population, would all benefit from increased collaboration. This work provides examples of how to nourish collaboration within the industry. More collaboration would foster increased consumer confidence, engagement, trust and industry growth. Barriers to collaboration include the current dominance of competitive over collaborative working environments.